Assimilation as the Impact of Diaspora Reflected in Mrs. Parker’s Family in Karate Kid Film - Baldatun, Ikhsan; Murtiningrum, Afina (LPPM Universitas Advent Indonesia, 2021)
Concerning the major issue as to how the diasporan group faces the assimilation, diaspora brings to mind several assumptions; it can be positive and negative to adapting one’s identity. Diaspora gets affected by some aspects of life such as culture, language, people, and place. The immigrants who moved or scattered from their home countries depend on how they can adapt to the new cultures, languages, and so on to new communities in the host countries that are different from theirs. This study aims to find out how the impact of diaspora perceived by analyzed the main characters during their process of diaspora. The approach of this study was descriptive qualitative research through the process of gathering the data qualitatively and reporting them descriptively. This study shows how the issue of diaspora relates to assimilation as the impact of the diaspora is reflected in Karate Kid film. The result of this study showed that the diasporan group integrates and possible to become a new type of human being as an immigrant in the new land. It represents assimilation in adoption values that exist in the host country.